THE INFLUENCE OF BRAND COMMUNITY INTEGRATION FOR BRAND LOYALTY IN THE COMMUNITY OF MATIC MOTORCYCLE YAMAHA MIO FAN CLUB MALANG - Aldhiki Meytena; Ikhtiara Kaideni Isharina (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The purpose of this study is to investigate and analyze the influence of brand community integration for brand loyalty in the community matic motorcycle Yamaha Mio Fan Club Malang (MFCM), either simultaneously or partially. In addition to knowing the variables that have a dominant influence. This study used a sample whole community Fan Club Mio Malang. Test is used to test the research instrument is test validity, test reliability, and test assumptions comprising classical normality test heterocedastisity, multikolenieritas test and autocorrelation test. Hypothesis testing using F test and t test. To analyze the test data is used multiple linear regression. The analysis showed that the simultaneous and significant brand community integration affects brand loyalty Yamaha Mio. Partially, brand community integration (product, brand, company, other consumers in the brand) have a significant influence on brand loyalty Yamah Mio. While that is dominant in the brand community integration in influencing brand loyalty is a product.